Epidemiological Aspects and Factors Associated with Early Neonatal Death From 2018 to 2020 in the Maternity of the Savè-Ouessè Health Zone, Benin, West Africa - Serge, Toudonou; Barikissou Georgia, Damien; Badirou, Aguemon (Journal of Maternal and Child Health, 2023)
Background: Most of the new-born deaths occur in developing countries where care access is poor. This study aimed to investigate the epidemiological aspects and factors associated with early neonatal death in maternity. Subjects and Method: A case-control study was conducted from 2018 to 2020 in the Savè-Ouessè (SaO) health zone in the Collines department in Benin. Two groups of new-borns aged 0-7 days were recruited, 176 cases and 176 controls. The dependent variable was early neonatal death. The main independent variables studied were related socio-demographic characteristics, medical and gynaeco-obstetric history, pregnancy-related illnesses, service use and quality of health care, and neonatal parameters. Data collection was carried out from October to December 2021 from delivery records at the maternity unit level. An additional questionnaire was addressed to corresponding mothers. Logistic regression model was used to identify factors that explain early neonatal death occurrence. Results: No Fertility desire (OR= 3.22; CI95%= 1.13 to 9.16; p =0.029); No Observance of ANC rhythms (OR= 5.14; CI95%= 1.63 to 16.15; p= 0.005); Supervised intake of SP (OR= 6.33; CI95%= 1.33 to 29.99; p<0.001); No Existence of active fetal movements (OR= 7.01; CI95%= 2.67 to 18.41; p<0.001); and Amniotic fluid colour/ Haematic (OR= 4.09; CI95%= 2.07 to 9.63; p<0.001) increased early neonatal death in SaO health zone from 2018 to 2020 in SaO health zone, BeninConclusion: Even if early neonatal mortality appears to be low in the SaO health zone, its reduction requires to strengthen family planning, to improve the observance of intermittent preventive treatment and to monitor obstetric labour. Keywords: perinatal death, early neonatal, death, associated factors, Benin. Correspondence:Damien Barikissou Georgia. Population Training and Research, University of Abomey-Calavi, Benin. Email: barikiss2000@yahoo.fr.